REGIONAL FINANCIAL PERFORMANCE ANALYSIS OF NORTH KALIMANTAN PROVINCE 2015-2019 - Chaniago, Jessica; Darmawati, Sri Sapto (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2022)
Analysis of regional financial performance is needed to determine the ability of regional governments in implementing regional autonomy. The implementation of good autonomy has an impact on the level of community welfare and the progress of the regional economy. This study aims to analyze the financial performance of the local government of North Kalimantan Province in 2015-2019. This study uses secondary data in the form of the Regional Revenue and Expenditure Budget Report and the 2015-2019 Budget Realization Report published by the Directorate General of Fiscal Balance through the official website www.djpk.kemenkeu.go.id using quantitative descriptive analysis. The analytical tools used are the ratio of regional independence, decentralization ratio, income growth ratio, expenditure suitability analysis, economic ratio, efficiency ratio,The results of this study areThe performance of the North Kalimantan Provincial Government in 2015-2019 can be said to be quite good. The ratios that can be said to be quite good are the ratio of fiscal decentralization, the ratio of income growth, the ratio of suitability of spending, the ratio of the economy, and the ratio of effectiveness. While the ratio is not good, namely the ratio of regional independence and efficiency ratio.